Sistem Pendukung Keputusan Penerimaan Mahasiswa Baru Universitas Harapan Dengan Menggunakan Metode PSI - Rafi Jariansyah; Muhammad Wahyu Hidayat; Wahyu Cavin Gunawan; Yessi Fitri Annisah Lubis; David David (LKP Unity Academy, 2025)
The new student selection process is very important to ensure the quality of prospective students accepted into universities. Harapan University considers various factors, such as high school majors (science, social sciences, or TKJ), academic test results, interviews, diplomas, and academic and extracurricular achievements. The manual approach that is still often used tends to be time-consuming, inefficient, and prone to errors. This study aims to develop a decision support system based on the Preference Selection Index (PSI) method to improve the effectiveness and efficiency of the selection process. The PSI method was chosen because of its ability to evaluate criteria directly without requiring weighting. The results of the study show that the PSI approach is able to produce the best candidate rankings based on predetermined criteria. This system offers a more organized, transparent, and accurate solution in the new student selection process.